Efforts to Improve Mathematical Communication Skills in Mathematics Learning in Indonesia - Epih, Epih Purnamasari (AB-JME: Al-Bahjah Journal of Mathematics Education, 2024)
This research aims to identify various models/methods/strategies and media that are effective in improving mathematical communication. This study uses the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) method with four stages, namely identification, scanning, eligibility, and inclusion. Harzing's Publish or Perish (PoP) is used to search for required research references. The research results found 30 publications regarding efforts to improve mathematical communication skills in schools and universities. Realistic Mathematic Education (RME), cooperative learning models, and the use of media are the methods most widely used in efforts to improve mathematical communication skills. Quantum learning models/methods, PBL, generative learning models, CBL, BBL, discovery, inquiry, and SSCS can also be chosen as alternatives in efforts to improve mathematical communication skills. Middle school level and geometry materials are most often used by researchers in efforts to improve mathematical communication. The results of this research can be a reference for teachers to choose the right model/method/strategy and media to improve mathematical communication skills in pupils and students.